Absence of Effect of Somatostatin Analogue (SMS 201-995) in Diarrhea Associated with Inflammatory Bowel Disease - Richard N. Fedorak; Richard W. Sherbaniuk (Canadian Journal of Gastroenterology)
The octapeptide long acting somatostatin analogue, SMS 201-995 promotes intestinal fluid and electrolyte absorption and inhibits anion secretion. It is more potent than native somatostatin and does not exhibit tachyphylaxsis. SMS 201-995 was used to treat two patients with severe diarrhea associated with Crohn’s disease after other treatments had failed. The volume and frequency of ileostomy output in one patient and stool output in the other did not respond to therapy with SMS 201-995. ln fact, diarrhea appeared to increase in both patients while on treatment.